Pemikiran Emanasi dalam Filsafat Islam dan Hubungannya dengan Sains Modern - Hasbi, Muhammad (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
This article deals with the sources of the theory of emanation or overflow (fayd) espoused by the Muslim philosophers and theologians to answer the question around the creation of the Universe, particularly on the generation of the universe from God. It will specifically investigate how Muslim philosophers have responded to the issue from either doctrinal or philosophical point of view. There are two major theories in the creation of universe; that it was created out of nothing and at some point of time in the past. The other theory believes in the creation of the universe out of prime substances and at no point in time in the past. The Muslim philosophers like al-Kindi and al-Farabi, as well as rational theologians like the Mu’tazilites hold the second theory. On the other hand, traditional theologians have the same belief with those who hold the first theory. In fact, newer findings from modern sciences through empirical observations, particularly in the field of physics and astronomy, have revealed that the second theory is more acceptable rationally than the first one. In other words, the theory that the universe was ever-created and created out of existed substances appears to be more compatible with modern theories of sciences on the same subject, particularly the “Big Bang” theory.